Action and Interaction between Retinoic Acid Signaling and Blood–Testis Barrier Function in the Spermatogenesis Cycle - Yu Zhou; Yunyan Wang (Cells, 2022)
Spermatogenesis is a complex process occurring in mammalian testes, and constant sperm production depends on the exact regulation of the microenvironment in the testes. Many studies have indicated the crucial role of blood–testis barrier (BTB) junctions and retinoic acid (RA) signaling in the spermatogenesis process. The BTB consists of junctions between adjacent Sertoli cells, comprised mainly of tight junctions and gap junctions. In vitamin A-deficient mice, halted spermatogenesis could be rebooted by RA or vitamin A administration, indicating that RA is absolutely required for spermatogenesis. Accordingly, this manuscript will review and discuss how RA and the BTB regulate spermatogenesis and the interaction between RA signaling and BTB function.